[問題]三角函數

[問題]三角函數

qeypour 於 星期日 四月 02, 2006 8:29 pm


f(n)=(sinx)^n+(cosx)^n

試證:[f(5)-f(3)]/f(1)=[f(7)-f(5)]/f(3)

qeypour
大 師
大 師
 
文章: 431
註冊時間: 2005-07-23

Re: [問題]三角函數

☆ ~ 幻 星 ~ ☆ 於 星期日 四月 02, 2006 10:20 pm


qeypour 寫到:f(n)=(sinx)^n+(cosx)^n

試證:[f(5)-f(3)]/f(1)=[f(7)-f(5)]/f(3)


左鍵: 點擊縮放; 右鍵: 觀看原圖

☆ ~ 幻 星 ~ ☆
教 授
教 授
 
文章: 1068
註冊時間: 2005-08-24

Re: [問題]三角函數

qeypour 於 星期日 四月 02, 2006 11:26 pm


☆ ~ 幻 星 ~ ☆ 寫到:
qeypour 寫到:f(n)=(sinx)^n+(cosx)^n

試證:[f(5)-f(3)]/f(1)=[f(7)-f(5)]/f(3)


左鍵: 點擊縮放; 右鍵: 觀看原圖

 

謝謝~~~~~~~~~~~


qeypour
大 師
大 師
 
文章: 431
註冊時間: 2005-07-23

p 於 星期一 四月 03, 2006 6:57 pm


另解
[f(5)-f(3)]/f(1)
= [(sinx)^5+(cosx)^5-(sinx)^3-(cosx)^3]/ [sinx+cosx]
={(sinx)^3[(sinx)^2-1]+(cosx)^3[ (cosx)^2-1]}/ [sinx+cosx]
={(sinx)^3[-(cosx)^2]+(cosx)^3[-(sinx)^2]}/ [sinx+cosx]
=-(sinx)^2*(cosx)^2*(sinx+cosx)/ [sinx+cosx]
=-(sinx)^2*(cosx)^2

[f(7)-f(5)]/f(3)
= [(sinx)^7+(cosx)^7-(sinx)^5-(cosx)^5]/ [(sinx)^3+(cosx)^3]
={(sinx)^5[(sinx)^2-1]+(cosx)^5[ (cosx)^2-1]}/ [(sinx)^3+(cosx)^3]
={(sinx)^5[-(cosx)^2]+(cosx)^5[-(sinx)^2]}/ [(sinx)^3+(cosx)^3]
=-(sinx)^2*(cosx)^2*[(sinx)^3+(cosx)^3]/ [(sinx)^3+(cosx)^3]
=-(sinx)^2*(cosx)^2

可推廣至
[f(5)-f(3)]/f(1)= [f(2k+3)-f(2k+1)]/f(2k-1), k=1,2,3,4,---
甚至推廣至偶數
[f(5)-f(3)]/f(1)= [f(2k+4)-f(2k+2)]/f(2k), k=1,2,3,4,---

綜合得
[f(5)-f(3)]/f(1)= [f(m+4)-f(m+2)]/f(m), m=0,1,2,3,4,---

p
訪客
 

qeypour 於 星期一 四月 03, 2006 7:24 pm


p 寫到:另解
[f(5)-f(3)]/f(1)
= [(sinx)^5+(cosx)^5-(sinx)^3-(cosx)^3]/ [sinx+cosx]
={(sinx)^3[(sinx)^2-1]+(cosx)^3[ (cosx)^2-1]}/ [sinx+cosx]
={(sinx)^3[-(cosx)^2]+(cosx)^3[-(sinx)^2]}/ [sinx+cosx]
=-(sinx)^2*(cosx)^2*(sinx+cosx)/ [sinx+cosx]
=-(sinx)^2*(cosx)^2

[f(7)-f(5)]/f(3)
= [(sinx)^7+(cosx)^7-(sinx)^5-(cosx)^5]/ [(sinx)^3+(cosx)^3]
={(sinx)^5[(sinx)^2-1]+(cosx)^5[ (cosx)^2-1]}/ [(sinx)^3+(cosx)^3]
={(sinx)^5[-(cosx)^2]+(cosx)^5[-(sinx)^2]}/ [(sinx)^3+(cosx)^3]
=-(sinx)^2*(cosx)^2*[(sinx)^3+(cosx)^3]/ [(sinx)^3+(cosx)^3]
=-(sinx)^2*(cosx)^2

可推廣至
[f(5)-f(3)]/f(1)= [f(2k+3)-f(2k+1)]/f(2k-1), k=1,2,3,4,---
甚至推廣至偶數
[f(5)-f(3)]/f(1)= [f(2k+4)-f(2k+2)]/f(2k), k=1,2,3,4,---

綜合得
[f(5)-f(3)]/f(1)= [f(m+4)-f(m+2)]/f(m), m=0,1,2,3,4,---

3Q~~~~~~~~~~~~~~~


qeypour
大 師
大 師
 
文章: 431
註冊時間: 2005-07-23






解析幾何及三角函數